Efforts of Tahfizh Teachers in Improving Students’ Ability to Memorize The Quran at Muhammadiyah Al-Kautsar PK Kartasura Junior High School - Hasan, Fadhilah; Inayati , Nurul Latifatul (FKIP - Universitas Riau, 2025)
Memorizing the Quran is a fundamental aspect of Islamic education that requires serious attention, particularly at the junior high school level, where students are in a critical stage of character and skill development. This study investigates the efforts of tahfizh teachers at Muhammadiyah Al-Kautsar PK Junior High School in Kartasura in improving students’ ability to memorize the Quran. The research emphasizes the important role of tahfizh teachers, who act not only as facilitators but also as motivators and mentors in guiding students through the memorization process. Using a qualitative descriptive approach, data were collected through observations, in-depth interviews, and documentation to gain a comprehensive understanding of the strategies applied. The findings reveal that teachers employ multiple methods to enhance memorization, such as correcting students’ recitations, modeling accurate pronunciation, applying memorization techniques like direct learning, repetition or drilling, and illiterate or unlettered, as well as encouraging consistent quran review. These efforts significantly improve the accuracy, fluency, and spirit of Quran memorization among students. In conclusion, the active involvement of tahfizh teachers through varied methods plays a decisive role in strengthening students’ memorization skills. Therefore, continuous development of teaching strategies and professional capacity building is essential to sustain effective Quran memorization learning.